2021
DOI: 10.1016/j.lanepe.2021.100129
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric outpatient prescriptions in France between 2010 and 2019: A nationwide population-based study

Abstract: Background Paediatric outpatient prescription (POP) monitoring is pivotal to identify inadequate prescriptions and optimize drug use. We aimed at describing recent trends in POPs in France. Methods All reimbursed dispensations of outpatient prescribed drugs (excluding vaccines) were prospectively collected for the paediatric population (<18 years old) in the French national health database in 2010–2011 and 2018–2019 (mean 117,356,938/year). POP prevalence (proportion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 54 publications
(69 reference statements)
1
37
0
Order By: Relevance
“… 19 , 20 , 22 , 34 , 37 , 38 Websites of institutes of public health or drug agencies provided annual national POP prevalence for 5 countries (eTable 2 in the Supplement ). 39 , 40 , 41 , 42 , 43 The 11 included studies 19 , 20 , 22 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 43 performed in 11 different countries ( Table 1 ) were based on data for 35 552 550 pediatric patients from North America, 34 , 38 Europe, 19 , 37 , 39 , 40 , 41 , 42 , 43 and New Zealand. 20 There were 3 regional studies 34 , 37 , 38 and 8 national studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… 19 , 20 , 22 , 34 , 37 , 38 Websites of institutes of public health or drug agencies provided annual national POP prevalence for 5 countries (eTable 2 in the Supplement ). 39 , 40 , 41 , 42 , 43 The 11 included studies 19 , 20 , 22 , 34 , 37 , 38 , 39 , 40 , 41 , 42 , 43 performed in 11 different countries ( Table 1 ) were based on data for 35 552 550 pediatric patients from North America, 34 , 38 Europe, 19 , 37 , 39 , 40 , 41 , 42 , 43 and New Zealand. 20 There were 3 regional studies 34 , 37 , 38 and 8 national studies.…”
Section: Resultsmentioning
confidence: 99%
“… 20 There were 3 regional studies 34 , 37 , 38 and 8 national studies. 19 , 20 , 22 , 39 , 40 , 41 , 42 , 43 Data were collected between 2002 and 2019 and after 2010 for 7 studies. 20 , 22 , 39 , 40 , 41 , 42 , 43 Eight studies 19 , 20 , 37 , 39 , 40 , 41 , 42 , 43 reported annual overall POP prevalence, and 8 studies 19 , 20 , 22 , 39 , 40 , 41 , 42 , 43 reported annual prevalence by level 1 of ATC classification, 9 studies 19 , 20 , 22 , 34 , 38 , 40 , 41 , 42 , 43 by level 2, and 7 studies 20 , 22 , 39 , 40 , 41 , 42 , 43 by level 5 ( Figure 1 and Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As in France, codeine was the most often prescribed opioid in all these countries except Denmark, where tramadol predominated. Other studies have shown higher prevalence of outpatient treatment prescriptions in France, and in particular analgesic therapy in children [ 13 , 14 ]. This can be explained by different reimbursement systems among countries [ 15 ].…”
Section: Discussionmentioning
confidence: 99%